Prototype of Wireless Sensor Networks as a Monitoring System for Environmental Conditions in Buildings - Ari Kusyanti; Kasyful Amron; Reza Andria Siregar (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The development of a wireless sensor network prototype as a monitoring system for environmental conditions in buildings is made to see and monitor sensors working inside the building centrally. This system uses several sensors such as DHT 11, MQ7. The ESP32 microcontroller is used as a gateway that collects data from sensor nodes by utilizing BLE communication media. Data from the gateway will be sent via wi-fi which will be displayed on a Grafana-based website. In this study, this implementation can be applied and used to monitor the state of the building by displaying temperature data and carbon dioxide levels.